Silica nanoparticles induce spermatocyte cell apoptosis through microRNA-2861 targeting death receptor pathway. (August 2019) - Ren, Lihua; Zhang, Jin; Wang, Ji; Wei, Jialiu; Liu, Jianhui; Li, Xiangyang; Zhu, Yupeng; Li, Yanbo; Guo, Caixia; Duan, Junchao; Sun, Zhiwei; Zhou, Xianqing
Abstract: Silica nanoparticles (SiNPs) are found in the environmental particulate matter and have been proved to pose an adverse effect on fertility. However, the relationship between miRNA and apoptosis induced by SiNPs in spermatogenesis and its underlying mechanism remains confusing. Therefore, the present study was designed to investigate the toxic effects of SiNPs on spermatogenic cells mediated through miRNAs. Spermatocyte cells were divided into 0 μg/mL and 5 μg/mL SiNPs groups, and the cells were collected and analyzed after passaging for 1, 10, 20, and 30 generations. miRNA profile and mRNA profile of spermatocyte cells were measured after exposure to SiNPs for 30 generations. Further, mimics and inhibitors of miRNA were used to verify the relationship between miRNA and their predicted target genes in the 30th-generation cells. The results showed that the degree of cell apoptosis in the SiNPs group significantly increased in the 30th generation. After exposure to SiNPs for 30 generations, the expression of 15 miRNAs was altered, including 5 upregulated miRNAs and 10 downregulated miRNAs. Of the 15 miRNAs, miR-138 and miR-2861 were related to the death receptor pathway. The miR-2861 mimic could target to regulate the mRNA expression of fas/fasl/ripk1 and increase the protein expression of Fas/FasL/RIPK1/FADD/caspase-8/caspase-3 of spermatogenic cells in the 30th generation, while the miR-138 inhibitor could not. In conclusion, SiNPs could cause apoptosis of spermatocyte cells by inhibiting the expression of miRNA-2861, thereby resulting in the upregulation of mRNA expression of fas/fasl/ripk1 and activating the death receptor pathway of spermatocyte cells . miRNA-2861 could be considered a biomarker of the toxic effect of SiNPs on spermatocyte cells. The main finding: Silica nanoparticles induce apoptosis in spermatocyte cells through microRNA-2861 inhibition, thereby upregulating mRNA expression of fas/fasl/ripk1 and activating the death receptor pathway of spermatocyte cells. Graphical abstract: Image 1 Highlights: The present study of SiNPs' toxicity on spermatocyte cell was designed from the point of epigenetic regulation. This work investigates the unique toxicity of repeated exposure to silica nanoparticles for 30 generations. Our research found that SiNPs could induce spermatocyte cell toxicity and lead to expression changes of 15 miRNAs. miRNA-2861 may be used as a biomarker of SiNPs-induced spermatocyte cell apoptosis through the RIPK1 signaling pathway.